If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2j + 3) = 3(6j + 9) Reorder the terms: 9(3 + 2j) = 3(6j + 9) (3 * 9 + 2j * 9) = 3(6j + 9) (27 + 18j) = 3(6j + 9) Reorder the terms: 27 + 18j = 3(9 + 6j) 27 + 18j = (9 * 3 + 6j * 3) 27 + 18j = (27 + 18j) Add '-27' to each side of the equation. 27 + -27 + 18j = 27 + -27 + 18j Combine like terms: 27 + -27 = 0 0 + 18j = 27 + -27 + 18j 18j = 27 + -27 + 18j Combine like terms: 27 + -27 = 0 18j = 0 + 18j 18j = 18j Add '-18j' to each side of the equation. 18j + -18j = 18j + -18j Combine like terms: 18j + -18j = 0 0 = 18j + -18j Combine like terms: 18j + -18j = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4s-3s=2 | | 35+8a=-7(8a-5) | | 6z-4z=12 | | 2h-16=3h-6 | | 87=5(3+x)+4x | | (2/5)+(7/8)=(y/20) | | 100y+15=75y+17x | | x=-0.5+-2 | | (7x+14)+26+(180-(10+10x))=180 | | e^11x-1=(e^9)x | | 2d+2=5d-11 | | 2/3x=-5 | | 100y+15=75y+17 | | 4x+21=7y | | 2.5x+4.5=8 | | 7x^2+20x+3=0 | | Y=5/8b+10 | | 10+1/4y=3/4y-6 | | 54t-12t^2= | | 2n-6= | | 12y=-6(-0.5+2y)-3 | | -16x^2+4+3= | | 21.3n-8.1n+2.2n-28.5=1.6(n+5n)-5.3 | | 5(x+1)=-45+4x | | 4m-16=2m-2 | | 3/4x=6 | | -16x^2+k+3= | | 3x+5=104 | | 4k+11=6k+3-2k | | 2.5-7.5y=6 | | 8x+30=2x-6 | | f(x)=2x-3 |